Disaster Risk Assessment of Informal Settlements in the Global South - Quesada Román, Adolfo (2022)
More than a billion people live in informal settlements worldwide. Their high exposure and vulnerability increase the risk of disaster in their lives. Global changes challenge the capacity to seek practical and quick solutions for the most disadvantaged groups. Most people in Costa Rica reside in the Greater Metropolitan Area (GAM, or Gran Área Metropolitana in Spanish), and nearly half of the informal settlements of the country are also located there. This paper aims to determine the disaster risk of every informal settlement of the GAM in Costa Rica. The study merges the official information that is available to calculate the hazard, exposure, vulnerability, and the risk levels of every informal settlement in the GAM. Moreover, a risk index for informal settlements in the GAM was created using a Pearson correlation technique, normalizing, and spatially distributing the results in three groups (high, medium, and low). The study outputs indicate that municipalities with a greater number of informal settlements also concentrate the higher risk unit’s percentage. Moreover, a direct statistical relationship is present between the historical number of disaster events in the municipalities with more informal settlements. The urban context proves useful to apply a methodology that could determine the disaster risk level of informal settlements in less-developed countries where baseline information for hazard, exposure, and vulnerability calculation is usually scarce, limited, or low in quality. This research shows the conditions of dozens of countries belonging to the Global South and constitutes a useful example for all of the stakeholders of disaster risk reduction worldwide.